External influences on the development and professionalisation of accounting in Malaysia, 1957-1969 - Azham Md. Mi; Lee Teck Heang; Brian West (Universitas Trisakti, 2011)
The accounting history literature identifies a tendency for accounting in developing countries to be dominated by the style of accounting institutions and practices of western developed nations - particularly the USA and UK.This